Verbal and Non-verbal Signs of “AQUA Life: Care for Nature, Nature Cares for You” - Ni Nyoman Sayun Trinadi; Desak Putu Eka Pratiwi; I Made Perdana Skolastika (Austronesian: Journal of Language Science & Literature, 2022)
This study aims to analyze the verbal and non-verbal signs as well as the meaning contained in the “AQUA Life: Care for Nature, Nature Cares for You” Advertisement. This study used a qualitative method. An observation method was used to collect the data. The data were taken from the YouTube platform. In analysing the verbal and non-verbal signs based on the Saussure’s semiotic theory while in analyzing the meaning of the verbal and non-verbal signs based on the Barthes’s theory. In addition, the study of colors was done using the approach of color term submitted by Cerrato. As the result, the researchers found three verbal signs and three non-verbal signs in this advertisement. The advertiser highlighted the advertised product in this advertisement, attempting to persuade the viewers that using 100% recycled products is one of the essential things to protect this planet. Furthermore, this advertisement also emphasized the importance of consuming mineral water for body health. From the analysis, it can be concluded that the “AQUA Life: Care for Nature, Nature Cares for You” advertisement employed meaningful sentences to gain the attention of their target consumers.